A 66-Year-Old Woman with a Progressive, Longitudinally Extensive, Tract Specific, Myelopathy - Elizabeth O’Keefe; Katherine E. Schwetye; John Nazarian; Richard Perrin; Robert E. Schmidt; Robert Bucelli (Case Reports in Neurological Medicine)
A 66-year-old woman presented with progressive lancinating pain and sensory deficits attributable to a myelopathy of unclear etiology. Spinal cord magnetic resonance imaging showed a longitudinally extensive T2-hyperintense lesion of the dorsal columns. Comprehensive serum, urine, and cerebrospinal fluid analyses failed to identify an etiology. Empiric intravenous methylprednisolone and intravenous immunoglobulin were of no benefit and serial screens for an occult malignancy were negative. She developed dysesthesias and allodynia affecting her entire body and lost the use of her arms and legs due to severe sensory ataxia that was steadily progressive from onset. She opted against additional aggressive medical management of her condition and passed away on hospice eleven months after symptom onset. Autopsy revealed findings most consistent with polyphasic spinal cord ischemia affecting the dorsal and lateral white matter tracts and, to a lesser extent, adjacent gray matter. The underlying etiology for the progressive vasculopathy remains unknown. Spinal cord ischemia affecting the posterior spinal cord is rare and to our knowledge this case represents the only instance of a progressive spinal cord tractopathy attributable to chronic spinal cord ischemia.